Estudo da estrutura e propriedades magnéticas de ferritas de Ni2+/Zn2+ dopadas com Nd3+ - Gomes Filho, Alberto Correia (2014)
The work consisted in the synthesis of ferrites of composition Ni0,5-xNdxZn0,5Fe2O4 varying the concentration of neodymium ions (Nd3+) for 0 ≤ x ≤ 0.3, the method being chosen as the citrate precursor method or route of synthesis. After synthesis, the samples were calcined at 350°C and then pressed into discs and toroids. Subsequently these samples were sintered at 1000°C for 3 hours, the rate being controlled heating and cooling. The calcined materials were characterized by XRD, SEM and vibrating sample magnetometry (MAV) and sintered samples by XRD, SEM, MAV, and measures of permeability and magnetic losses. The method of the precursor citrate has been demonstrated to be an effective method because obtained structural materials with desirable features. From XRD and the Rietveld refinement, it was found that the synthesized samples and treated at 350°C showed 100% formation of the single phase of spinel type and treated at 1000°C showed besides the ferrite phase, secondary phase confirmed by refinement as NdFeO3. The samples treated at 1000°C for 3 hours have passed the dimensions in micrometers due to the diffusion effect between the crystals, which increases at higher temperatures. The synthesized and treated at 350 and 1000°C for 3 hours ferrites behave as magnetically "soft" or "soft" and intensity of saturation magnetization decreases with the increase in the samples of neodymium (Nd3+) materials. The proof of this decrease was demonstrated by the study of positioning of cations in the spinel network using the Rietveld refinement method, and the influence of these changes in the magnetic properties, from the comparative relationship between the magnetization values in terms of the Bohr magneton theoretical (MBTeórico) and experimental Bohr (MBExp.). The results of electrical tests of the synthesized samples showed that the materials developed have potential for miniaturization for applications in electronic devices such as inductive microwave in telecom cores